Filsafat dalam Pemecahan Masalah Pendidikan - Ajito, Timoteus; Atmaja, Ananta Wikrama Tungga; Suastra, Wayan; Tika, I Nyoman (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Philosophy and education have a very close relationship where education and philosophy cannot be separated from each other because both are interdependent. Education without a philosophical foundation is just a concept without providing practical impact through education. Thus, this symbiotic relationship is very important to develop a comprehensive, meaningful, and impactful education system. Therefore, the importance of integration between education and philosophy. To ensure that educational efforts and educational processes run effectively, a philosophical and scientific foundation is needed as a principle and normative guideline for implementing training. This paper aims to describe the philosophical view in solving educational problems. This research method uses a literature review by collecting literature from various sources related to the philosophical view of education. The data analysis technique used is narrative analysis. The study results show that, for education to run effectively, an intellectual and scientific foundation is needed as a principle and normative guideline for implementing training. This means that, overall, an understanding of the philosophy of education is crucial for an educator. It helps them understand the goals of education, choose the right teaching methods, and understand their roles and responsibilities as quality educators